Acute Hemolytic Transfusion Reaction by an Anti-s Due to Delayed Type and Screen Procedures Until Occurrence of a Hemorrhagic Shock - Zimmermann, Robert; Strasser, Erwin; Hackstein, Holger (Transfusionsmedizin, 2019)
In the past decade, profound changes in the clinical practice of haemotherapy have occurred in most industrial countries, including Germany. Red blood cell (RBC) order procedures are performed more and more cautious. The utilization of RBC concentrates is strongly declining. At the same time, the number of patients for whom the preoperative or pre-interventional provision of cross-matched blood is not carried out despite planned surgery or intervention is also increasing. We report on a 71-year-old multimorbid patient with dilated cardiomyopathy, severely reduced cardiac reserve, a few weeks after valve replacement surgery, ongoing anticoagulation with heparin and diagnosed anemia with hemoglobin values between 7 and 8 g/dl. In this patient, a haemorrhagic shock was induced by a Forrest-II b haemorrhage from a duodenal ulcer after several days of in-patient treatment. In the context of emergency care, it turned out that all pre-transfusion diagnostics had been missed. The patient received uncross-matched red blood cell concentrates of blood group 0 Rh negative which unexpectedly triggered an acute haemolytic transfusion reaction. The reason was an irregular antibody against the antigen s from the MNSs blood group system that had not been identified before the transfusion. Acute hemolytic transfusion reactions outside the AB0 system are a rare, but nevertheless always threatening complication of the transfusion of uncrossmatched erythrocyte concentrates in life- threatening bleeding emergencies. The case shows that the desire to follow a restrictive transfusion practice must not lead to overlooking constellations in individual cases which, of course, require the timely performance of a pre-transfusional diagnostic procedure with blood group typing, antibody screening and antibody identification. In our opinion, the frequency of comparable events is increasing to an extent that suggests that such errors in the clinical treatment process should not only be dealt within CIRS systems but also recorded in haemovigilance systems.
CRIS-Team WoS Importer:2019-09-20

Aggregates in platelet concentrates - Van Der Meer, P. F.; Dumont, L. J.; Lozano, Miguel; Bondar, N.; Wong, J.; Ismay, S.; Pink, J.; Nussbaumer, W.; Coene, J.; Feys, H. B.; Compernolle, V.; Devine, D. V.; et al. (Vox Sanguinis, 2015)
EVALuna2:15991

Association of an In-House Blood Bank with Therapy and Outcome in Severely Injured Patients: An Analysis of 18,573 Patients from the TraumaRegister DGU® - Debus, Florian; Lefering, Rolf; Lechler, Philipp; Schwarting, Tim; Bockmann, Benjamin; Strasser, Erwin; Mand, Carsten; Ruchholtz, Steffen; Frink, Michael (PLoS ONE, 2016)
INTRODUCTION: Hemorrhagic shock remains one of the most common causes of death in severely injured patients. It is unknown to what extent the presence of a blood bank in a trauma center influences therapy and outcome in such patients. MATERIAL AND METHODS: We retrospectively analyzed prospectively recorded data from the TraumaRegister DGU® and the TraumaNetzwerk DGU®. Inclusion criteria were Injury Severity Score (ISS) ≥ 16, primarily treated patients, and hospital admission 2 years before or after the audit process. RESULTS: Complete data sets of 18,573 patients were analyzed. Of 457 hospitals included, 33.3% had an in-house blood bank. In trauma centers with a blood bank (HospBB), packed red blood cells (PRBCs) (21.0% vs. 17.4%, p < 0.001) and fresh frozen plasma (FFP) (13.9% vs. 10.2%, p <0.001) were transfused significantly more often than in hospitals without a blood bank (Hosp0). However, no significant difference was found for in-hospital mortality (standard mortality ratio [SMR, 0.907 vs. 0.945; p = 0.25). In patients with clinically apparent shock on admission, no difference of performed transfusions were present between HospBB and Hosp0 (PRBCs, 51.4% vs. 50.4%, p = 0.67; FFP, 32.7% vs. 32.7%, p = 0.99), and no difference in in-hospital mortality was observed (SMR, 0.907 vs. 1.004; p = 0.21). DISCUSSION: In HospBB transfusions were performed more frequently in severely injured patients without positively affecting the 24h mortality or in-house mortality. Easy access may explain a more liberal transfusion concept.
EVALuna2:32780

Automated closed-system manufacturing of human monocyte-derived dendritic cells for cancer immunotherapy - Erdmann, Michael; Uslu, Ugur; Wiesinger, Manuel; Bruening, Mareke; Altmann, Tobias; Strasser, Erwin; Schuler, Gerold; Schuler-Thurner, Beatrice (Journal of Immunological Methods, 2018)
Dendritic cell (DC)-based vaccines have been successfully used for immunotherapy of cancer and infections. A major obstacle is the need for high-level class A cleanroom cGMP facilities for DC generation. The CliniMACS Prodigy® (Prodigy) represents a new platform integrating all GMP-compliant manufacturing steps in a closed system for automated production of various cellular products, notably T cells, NK cells and CD34+ cells. We now systematically tested its suitability for producing human mature monocyte-derived DCs (Mo-DCs), and optimized it by directly comparing the Prodigy approach to our established standard production of Mo-DCs from elutriated monocytes in dishes or bags. Upon step-by-step identification of an optimal cell concentration for the Prodigy's CentriCult culture chamber, the total yield (% of input CD14+ monocytes), phenotype, and functionality of mature Mo-DCs were equivalent to those generated by the standard protocol. Technician's labor time was comparable for both methods, but the Prodigy approach significantly reduced hands-on time and high-level clean room resources. In summary, using our optimized conditions for the CliniMACS Prodigy, human Mo-DCs for clinical application can be generated almost automatically in a fully closed system. A significant drawback of the Prodigy approach was, however, that due to the limited size of the CentriCult culture chamber, in contrast to our standard semi-closed elutriation approach, only one fourth of an apheresis could be processed at once.
EVALuna2:203616

Blood counts in adult and elderly individuals: defining the norms over eight decades of life - Zierk, Jakob; Krebs, Alexander; Rauh, Manfred; Metzler, Markus; Löscher, Astrid; Strasser, Erwin; Krause, Stefan (British Journal of Haematology, 2020)
The blood count is one of the most common tests used for health assessment. In elderly individuals, selection of a ‘healthy’ reference population for laboratory assessment is difficult due to the high prevalence of chronic morbidities, leading to uncertainty regarding appropriate reference intervals. In particular, age-specific lower haemoglobin reference limits to define anaemia are controversial. Here, we applied a data mining approach to a large dataset of 3 029 904 clinical routine samples to establish blood count reference intervals. We excluded samples from units/specialists with a high proportion of abnormal blood counts, samples from patients with an unknown or decreased estimated glomerular filtration rate, and samples with abnormal test results in selected other analytes. After sample exclusion, 566 775–572 060 samples from different individuals aged 20–100 years were available for analysis. We then used an established statistical algorithm to determine the distribution of physiological test results and calculated age- and sex-specific reference intervals. Our results show substantial trends with age in haematology analytes' reference intervals. Most notably, haemoglobin and red cell counts decline in men with advanced age, accompanied by increases in red cell volume in both sexes. These findings were confirmed in an independent dataset, and suggest an at least partly physiologic cause.
CRIS-Team Scopus Importer:2020-02-14
Keywords: anaemia; haematology; laboratory haematology

Blood counts in adults and elderly individuals - Zierk, Jakob; Krebs, A.; Rauh, Manfred; Metzler, Markus; Parsch, H.; Strasser, Erwin; Krause, Stefan (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Buffy coat volume reduction for optimization of leucapheresis harvests produced by the autoMNC program - Burk, Samaya; Erdmann, M.; Weiss, D.; Eckstein, Reinhold; Strasser, Erwin (Vox Sanguinis, 2015)
Buffy coat (BC) volume reduction was evaluated in leucapheresis (LA) harvests due to the target monocyte yield and the red blood cell (RBC) content. A packed erythrocyte volume (PEV) of 7.5 ml should not be exceeded to avoid RBC debulking with loss of leucocytes (WBCs) and the monocyte fraction during monocyte counterflow elutriation, a next step of monocyte enrichment prior to cell culture.Two hundred and fifty-three 5-l leucaphereses (autoMNC program) performed in 102 healthy blood donors (24 female and 78 male donors) were retrospectively analysed. Different categories of BC volumes were compared due to the quality of the LA products measured by blood counts and flow cytometry.Collection of maximum BC volume of 10 ml and more each collection cycle (product volume: 169 ± 21 ml) resulted in 1.58 ± 0·41 × 10e9 CD14(+) monocytes and high volume of packed erythrocyte (18.4 ± 8.8 ml). Low BC volume collection below 6 ml each collection cycle produced only 1.07 ± 0.40 × 10e9 CD14(+) monocytes but reduced PEV significantly by 64% (6.7 ± 4.1 ml).By reduction of the BC volume, the PEV in LA products could be reduced, which is a precondition for counterflow elutriation of monocytes. A BC volume between 7 and 8 ml per collection cycle should be adjusted to reduce PEV to 7.5 ml without relevant monocyte loss.
EVALuna2:15992

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Change of the metabolomic profile during short-term mononuclear cell storage - Steininger, Philipp; Strasser, Erwin; Ziehe, Bettina; Eckstein, Reinhold; Rauh, Manfred (Vox Sanguinis, 2017)
BACKGROUND AND OBJECTIVES: Short-term storage of leukapheresis products used for immunotherapeutic mononuclear cell (MNC) products is a frequent event. The analysis of time-related metabolic patterns enables the characterization of storage-related effects in MNCs and the hypothesis-based optimization of the MNC medium. MATERIALS AND METHODS: The MNC products from seven leukapheresis procedures were stored within a closed bag system for 48 h. Concentrations of amino acids, biogenic amines, phospho- and sphingolipids and hexoses in the medium were measured by targeted metabolomics. The viability of MNC subpopulations was assayed by Annexin V (AnV) and JC-1 staining. RESULTS: Glucose depletion and a significant change of the acylcarnitine profile are early events within the first 24 h of storage. In contrast, for most amino acids, the maximum increase was observed at 48 h of storage as mirrored by an increase in the amino acid levels by a mean factor of 1·2 (1·3, 2·0) after 6 h (24 h, 48 h, respectively). This was except for the concentrations of glutamine and lysine, which did not change significantly. The taurine concentration showed a twofold increase within the first 24 h and remained constant thereafter. The steepest increase in AnV+and 7-AAD+CD4+T cells was found between 24 and 48 h. CONCLUSION: The time-course of apoptosis and metabolic patterns in the MNC products demonstrate that 24 h of storage is a decisive time-point, as afterwards key metabolic pathways showed nonlinear detrimental changes. Optimization of storage by supplementation of specific substrates demands therefore an early intervention.
EVALuna2:32783

Closing the gap - Detection of clinically relevant von Willebrand disease in emergency settings through an improved algorithm based on rotational Thromboelastometry 11 Medical and Health Sciences 1103 Clinical Sciences 11 Medical and Health Sciences 1102 Cardiorespiratory Medicine and Haematology - Topf, H. -G.; Strasser, Erwin; Breuer, Georg; Rascher, Wolfgang; Rauh, Manfred; Fahlbusch, F. B. (BMC Anesthesiology, 2019)
Background: Hemorrhage and blood loss are still among the main causes of preventable death. Global hemostatic assays are useful point-of-care test (POCT) devices to rapidly detect cumulative effects of plasma factors and platelets on coagulation. Thromboelastography (TEG) and Thromboelastometry (ROTEM) are established methods in many anesthesiological departments for guided hemostatic treatment. However, von Willebrand disease remains undetected by standard ROTEM, especially during emergency care, despite being the most prevalent congenital hemostatic disorder. Methods: In our monocentric cohort pilot study we focused on hemostatic challenges associated with von Willebrand disease. Twenty-seven patients with suspected von Willebrand disease were included. We modified the routine ROTEM assay by adding a preincubation with ristocetin and commercially available plasma-derived von Willebrand factor to identify clinically relevant von Willebrand disease (VWD). Results: Addition of von Willebrand factor to the ristocetin assay of a VWD type 3 patient restored the reaction of the whole blood probe to match the response of a healthy person. Our modified ROTEM assay with ristocetin (Ricotem) showed that all high responders (n = 7) had VWD. In the low responder group (n = 16) - 10 of 16 had VWD and in the normal responder group (n = 5), 2 of 5 had mild type 1 VWD. Conclusions: This new modification of the standard ROTEM assay enables the detection of otherwise unnoticed critical von Willebrand disease based on alterations in clot formation and might serve as a novel approach to reliably assess severe VWD patients by platelet-mediated blood clotting in an emergency setting. We recommend incorporating this new VWD-focused screening tool into the current ROTEM-based management algorithm of acute microvascular bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Bleeding; Emergency; ROTEM; Thromboelastometry; Von Willebrand disease; VWD

Comparative morphology analysis of live blood platelets using scanning ion conductance and robotic dark-field microscopy - Kraus, Max-Joseph; Seifert, Jan; Strasser, Erwin; Gawaz, Meinrad; Schaeffer, Tilman E.; Rheinlaender, Johannes (Platelets, 2016)
Many conventional microscopy techniques for investigating platelet morphology such as electron or fluorescence microscopy require highly invasive treatment of the platelets such as fixation, drying and metal coating or staining. Here, we present two unique but entirely different microscopy techniques for direct morphology analysis of live, unstained platelets: scanning ion conductance microscopy (SICM) and robotic dark-field microscopy (RDM). We demonstrate that both techniques allow for a quantitative evaluation of the morphological features of live adherent platelets. We show that their morphology can be quantified by both techniques using the same geometric parameters and therefore can be directly compared. By imaging the same identical platelets subsequently with SICM and RDM, we found that area, perimeter and circularity of the platelets are directly correlated between SICM and dark-field microscopy (DM), while the fractal dimension (FD) differed between the two microscopy techniques. We show that SICM and RDM are both valuable tools for the ex vivo investigation of the morphology of live platelets, which might contribute to new insights into the physiological and pathophysiological role of platelet spreading.
EVALuna2:15995

Comparison of Simultaneous CD34+ and CD3+ Quantification with a Modified Stem Cell Enumeration Kit on Two Different Flow Cytometers - Strobel, Joachim; Hauck-Dlimi, Barbara; Weisbach, Volker Günter; Eckstein, Reinhold; Zingsem, Jürgen; Strasser, Erwin (Clinical Laboratory, 2016)
BACKGROUND: Quantification of CD34+ cells in peripheral blood stem cell apheresis is normally performed by single platform flow cytometric measurements according to the ISHAGE protocol. Peripheral blood stem cell concentrates (PBSC) produced by apheresis normally contain many T cells. Those T cells can be used for production of donor lymphocyte infusion doses, if abundant amounts of CD34+ cells have been collected. Therefore, it is of interest to know both the CD3+ and the CD34+ cell count of allogeneic PBSC. This is the first study comparing the performance of a modified ISHAGE protocol allowing additional quantification of CD3+ cells on two different flow cytometers, the FACSCalibur and the FACSVerse, respectively. METHODS: CD45+ and CD34+ cell concentrations were measured using a standard and a modified ISHAGE protocol including CD3+ cell quantification on both machines. All cell concentrations were measured using a Trucount bead based stem cell enumeration kit. The FACSVerse machine can additionally be equipped with a sample volume sensor allowing cell quantification without using beads. The samples analysed were taken from granulocyte-colony-stimulating factor mobilized peripheral blood stem cell apheresis procedures (pre- and post-apheresis, and apheresis concentrate). RESULTS: There were no significant differences in cell concentrations measured by the standard and modified ISHAGE protocol, regardless of which machine had been used when using bead quantification. No significant differences between the results of the two flow cytometers using the modified ISHAGE protocol were observed. Pearson´s correlation was always > 0.96, and regression coefficients were higher than 0.93. The only significant differences were observed between bead quantification and volume sensor quantification on the FACSVerse machine. CONCLUSIONS: The modified ISHAGE protocol can effectively be used on both flow cytometers tested, especially if bead quantification is used.
EVALuna2:32774

Contribution of MINCLE-SYK Signaling to Activation of Primary Human APCs by Mycobacterial Cord Factor and the Novel Adjuvant TDB - Ostrop, Jenny; Jozefowski, Katrin; Zimmermann, Stephanie; Hofmann, Katharina; Strasser, Erwin; Lepenies, Bernd; Lang, Roland (Journal of Immunology, 2015)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, is an abundant cell wall glycolipid and major virulence factor of Mycobacterium tuberculosis. Its synthetic analog trehalose-6,6-dibehenate (TDB) is a new adjuvant currently in phase I clinical trials. In rodents, the C-type lectin receptors Mincle and Mcl bind TDB/TDM and activate macrophages and dendritic cells (DC) through the Syk-Card9 pathway. However, it is unknown whether these glycolipids activate human innate immune cells through the same mechanism. We performed in vitro analysis of TDB/TDM-stimulated primary human monocytes, macrophages, and DC; determined C-type lectin receptor expression; and tested the contribution of SYK, MINCLE, and MCL by small interfering RNA knockdown and genetic complementation. We observed a robust chemokine and cytokine release in response to TDB or TDM. MCSF-driven macrophages secreted higher levels of IL-8, IL-6, CCL3, CCL4, and CCL2 after stimulation with TDM, whereas DC responded more strongly to TDB and GM-CSF-driven macrophages were equally responsive to TDB and TDM. SYK kinase and the adaptor protein CARD9 were essential for glycolipid-induced IL-8 production. mRNA expression of MINCLE and MCL was high in monocytes and macrophages, with MINCLE and MCL proteins localized intracellularly under resting conditions. Small interfering RNA-mediated MINCLE or MCL knockdown caused on average reduced TDB- or TDM-induced IL-8 production. Conversely, retroviral expression in murine Mincle-deficient DC revealed that human MINCLE, but not MCL, was sufficient to confer responsiveness to TDB/TDM. Our study demonstrates that SYK-CARD9 signaling plays a key role in TDB/TDM-induced activation of innate immune cells in man as in mouse, likely by engagement of MINCLE.
EVALuna2:7676

Data mining of reference intervals for coagulation screening tests in adult patients - Zierk, Jakob; Ganslandt, Thomas; Rauh, Manfred; Metzler, Markus; Strasser, Erwin (Clinica Chimica Acta, 2019)
Background: Appropriate reference intervals are essential when evaluating laboratory test results. However, establishment of reference intervals is challenging, especially for coagulation screening tests, and uncertainty exists regarding age- and sex-dependency of test results. Data mining of laboratory information systems is an emerging approach to reference interval determination, and we evaluated its applicability to coagulation tests. Methods: We analyzed measurements of activated partial thromboplastin time (aPTT), prothrombin time (PT), international normalized ratio (INR), thrombin time (TT), and fibrinogen performed during clinical care in the University Hospital Erlangen, Germany (1,778,738 samples from 116,754 adult patients, 45,577-509,859 samples per analyte). We identified the proportion of samples from healthy individuals using an established statistical approach (Reference Limit Estimator), in which the distribution of physiological test results is approximated using a parametrical function, and used for the calculation of reference intervals. Results: We established age- and sex specific reference intervals for aPTT, PT, INR, TT, and fibrinogen, and created batch- and reagent-specific aPTT-reference intervals. Additionally, we evaluated the sensitivity of the established aPTT reference intervals for the detection of factor VIII, IX, XI, XII deficiencies. Conclusion: Data mining of laboratory test results allows the creation of age- and sex-reference intervals for coagulation tests that are specific to the examined population, analytical framework, and reagent. This approach can complement conventional methods when establishing reference intervals and improve clinical decision-making based on coagulation tests. The reference intervals established in this study show only minor variation with sex and age, supporting the practice of providing a common reference interval for adult women and men.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Coagulation screening tests; Data mining; Reference intervals

Die neue Richtlinie Hämotherapie - Strasser, Erwin (Unfallchirurg, 2018)
The 2017 update of the German guidelines on hemotherapy is highly associated with the drug legislation and guidelines and thus necessitated a new structure of the contents. These guidelines reflect the state of the art for collection and application of blood and blood components corresponding to the Transfusion Act and is therefore the main document in hemotherapy. Topics of high interest in this 2017 update related to application of blood products are clarification and consent of patients, obligation for documentation, information, reporting and notification reports in the case of transfusion reactions and detailed description of quality management and quality assurance, as well as task description of persons responsible for the organization or implementation of transfusion-associated workflows. Surveillance, collating and management of errors are important prerequisites for the continuous optimization of patient safety. Patient blood management (PBM) as a requirement for the efficient use of blood products and the controlled and economical usage of autologous hemotherapy procedures (e. g. mechanical autotransfusion, MAT) are measures to reduce the need for blood products. All medical specialist societies, which carry out hemotherapy and participate in the standing committee of the Federal Medical Council (BÄK) to revise the hemotherapy guidelines have to take care that the guidelines are understandable for medical doctors and the transfusion team. Additionally, the core principles of hemotherapy have to be described in a clear and distinct manner.
EVALuna2:213432

Direct Oral Anticoagulant Plasma Levels for the Management of Acute Ischemic Stroke - Marsch, Armin; Macha, Kosmas; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd (Cerebrovascular Diseases, 2019)
Introduction: The management of acute ischemic stroke in patients on direct oral anticoagulants (DOACs) is challenging. However, the substance-specific plasma level could guide treatment decisions on recanalization therapies. We present a plasma-level-based protocol for emergency treatment of stroke patients on oral anticoagulants. Bleeding complications and clinical outcome for patients on DOACs are reported and compared to patients on vitamin K antagonists (VKAs). Methods: In patients with acute ischemic stroke and suspected use of DOACs within 48 h prior to hospital admission, plasma levels were measured using the calibrated Xa-activity (apixaban, edoxaban, rivaroxaban) or the Hemoclot®-assay (dabigatran). Levels <50 ng/mL were supportive for thrombolysis, while high values >100 ng/mL excluded patients from recombinant tissue plasminogen activator use. For patients on VKAs, the cutoff was set at international normalized ratio of 1.7. Endovascular thrombectomy of a large vessel occlusion was performed independently from coagulation testing. Consecutive patients were included in an observational registry. Results: Five hundred and twenty-two patients (261 on VKAs and 261 on DOACs) were included. Thirty patients (11.5%) on VKAs and 24 (9.2%) on DOACs received thrombolysis, followed by mechanical thrombectomy in 10 and 14 patients, respectively. Seventeen patients in each group received thrombectomy only. Symptomatic intracranial hemorrhage associated with thrombolysis occurred in 1 patient on VKA (3.3%) and 1 on DOAC (4.2%; p = 0.872). The turnaround time of specific assays did not show a significant delay in comparison to standard coagulation parameters. Conclusion: DOAC plasma levels could support decisions on emergency treatment of ischemic stroke. Systemic thrombolysis below suggested thresholds appears preliminary feasible and safe without an excess in bleeding complications.
CRIS-Team Scopus Importer:2019-09-24

First comparative analysis concerning the plasma platelet contamination during MNC collection - Pfeiffer, Hella; Achenbach, Susanne; Strobel, Joachim; Zimmermann, Robert; Eckstein, Reinhold; Strasser, Erwin (Transfusion and Apheresis Science, 2017)
BACKGROUND AND OBJECTIVES: Monocytes can be cultured into dendritic cells with addition of autologous plasma, which is highly prone to platelet contamination due to the apheresis process. Since platelets affect the maturation process of monocytes into dendritic cells and might even lead to a diminished harvest of dendritic cells, it is very important to reduce the platelet contamination. A new collection device (Spectra Optia) was analyzed, compared to two established devices (COM.TEC, Cobe Spectra) and evaluated regarding the potential generation of source plasma. MATERIALS AND METHODS: Concurrent plasma collected during leukapheresis was analyzed for residual cell contamination in a prospective study with the new Spectra Optia apheresis device (n=24) and was compared with COM.TEC and Cobe Spectra data (retrospective analysis, n=72). Donor pre-donation counts of platelets were analyzed for their predictive value of contaminating PLTs in plasma harvests. RESULTS: The newest apheresis device showed the lowest residual platelet count of the collected concurrent plasma (median 3.50×109/l) independent of pre-donation counts. The other two devices and sets had a higher platelet contamination. The contamination of the plasma with leukocytes was very low (only 2.0% were higher than 0.5×109/l). CONCLUSIONS: This study showed a significant reduction of platelet contamination of the concurrent plasma collected with the new Spectra Optia device. This plasma product with low residual platelets and leukocytes might also be used as plasma for fractionation.
EVALuna2:32782

First comparative evaluation of a new leukapheresis technology in non-cytokine-stimulated donors - Steininger, Philipp; Strasser, Erwin; Weiss, D.; Achenbach, Susanne; Zimmermann, Rüdiger; Eckstein, Reinhold (Vox Sanguinis, 2014)
Leukapheresis is an important source for mononuclear cells (MNCs) used in adoptive immunotherapies. Differences in the apheresis technology concerning physical conditions during cell separation and the optical detection system can affect the product's cellular content.In a paired analysis, twenty healthy non-cytokine-stimulated donors underwent MNC collection at the Spectra Optia (Terumo BCT, Lakewood, CO, USA) and the COM.TEC (Fresenius Kabi, Bad Homburg, Germany) device. In twelve donors, apheresis was additionally performed with the Amicus (Fenwal Inc., Lake Zurich, IL, USA). Donor response to leukapheresis and product composition was compared.Mean yields of CD14(+) (CD3(+) ) cells were 1·64 ± 0·70x10(9) (2·36 ± 0·96 × 10(9) ) in the Spectra Optia, 1·45 ± 0·50 × 10(9) (3·03 ± 1·04 × 10(9) ) in the COM.TEC and 1·20 ± 0·37 × 10(9) (2·80 ± 1·00 × 10(9) ) in the Amicus products, respectively. The Spectra Optia collected significantly more CD14(+) monocytes than the Amicus and significantly less CD3(+) T cells than the COM.TEC (P = 0·002 and P = 0·021). Apheresis products of the Spectra Optia showed the significantly lowest red blood cell yields while the Amicus generated products with the significantly lowest platelet contents.Leukaphereses with the three devices resulted in almost equal total MNC yields. MNC products of the Spectra Optia and the Amicus could be used in preference for the monocyte enrichment by the Elutra system and the leukapheresis procedures could be also favourably applied in patients with low platelet counts. The COM.TEC is more efficient in monocyte and T-cell collection with the disadvantage of high residual non-target cell content in the products.
EVALuna2:15968

Head and neck tumor cells treated with hypofractionated irradiation die via apoptosis and are better taken up by M1-like macrophages - Wedekind, Hanna; Walz, Kristina; Buchbender, Mayte; Rieckmann, Thorsten; Strasser, Erwin; Grottker, Fridolin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Rückert, Michael (Strahlentherapie und Onkologie, 2021)
Purpose: The incidence of head and neck squamous cell carcinomas (HNSCC) is increasing worldwide, especially when triggered by the human papilloma virus (HPV). Radiotherapy has immune-modulatory properties, but the role of macrophages present in HNSCC and having contact with irradiated tumor cells remains unclear. The influence of irradiated (2 × 5Gy) HNSCC cells on the (re-)polarization and phagocytosis of human macrophages, either non-polarized or with a more M1 or M2 phenotype, was therefore investigated. Methods: Human monocytes were differentiated with the hematopoietic growth factors M‑CSF (m) or GM-CSF (g) and additionally pre-polarized with either interleukin (IL)-4 and IL-10 or interferon (IFN)-γ and lipopolysaccharides (LPS), respectively. Subsequently, they were added to previously irradiated (2 × 5Gy) and mock-treated HPV-positive (UD-SCC-2) and HPV-negative (Cal33) HNSCC cells including their supernatants. Results: The HNSCC cells treated with hypofractionated irradiation died via apoptosis and were strongly phagocytosed by M0m and M2 macrophages. M0g and M1 macrophages phagocytosed the tumor cells to a lesser extent. Irradiated HNSCC cells were better phagocytosed by M1 macrophages compared to mock-treated controls. The polarization status of the macrophages was not significantly changed, except for the expression of CD206 on M2 macrophages, which was reduced after phagocytosis of irradiated HPV-negative cells. Further, a significant increase in the uptake of irradiated HPV-positive cells by M0g macrophages when compared to HPV-negative cells was observed. Conclusion: HNSCC cells treated with hypofractionated irradiation foster phagocytosis by anti-tumorigenic M1 macrophages. The data provide the first evidence on the impact of the HPV status of HNSCC cells on the modulation of the macrophage response to irradiated tumor cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Head and neck cancer; Human papilloma virus; Macrophage polarization; Phagocytosis; Radiotherapy

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Impact of collection programs for the generation of monocyte apheresis products on product quality and composition as starting material for the generation of cellular therapeutics - Pfeiffer, Hella; Gary, Regina; Mackensen, Andreas; Achenbach, Susanne; Strasser, Erwin; Aigner, Michael; Völkl, Simon (Transfusion, 2018)
BACKGROUND: With the discontinuation of the last generation of apheresis machines, new options for monocyte apheresis became available. As apheresis products play a crucial role in the generation of new cellular therapeutics (e.g., generation of dendritic cells [DCs] or precursor for T-cell experiments) we sought to compare two different collection programs for potential benefits or disadvantages due to different composition of the cellular products. STUDY DESIGN AND METHODS: Composition of discontinuously and continuously collected monocyte products from the same 13 donors was analyzed. For further evaluation as starting material for manufacturing of cellular therapeutics typically used steps such as Ficoll Isopaque, cryoconservation and monocyte isolation, with subsequent generation of mature DCs (mDCs) and assessment of T-cell function, were performed on seven of these apheresis pairs. RESULTS: Yield of total cells, monocytes, and mDCs was equal with both methods. T-cell composition did not differ significantly in content of CD3+, CD4+, and CD8+ cells. Differentiation status and cytokine production of CD8+ T cells upon stimulation with cytomegalovirus pp65 antigen was not significantly different. CONCLUSION: Both methods seem comparably suited for the generation of cellular products. If the intended use is "fresh" (without cryoconservation), continuously harvested cells show better cell numbers, while discontinuously harvested cells show better recovery after cryoconservation.
EVALuna2:34646

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation - Stoll, Svenja; Macha, Kosmas; Marsch, Armin; Gerner, Stefan; Siedler, Gabriela; Fröhlich, Kilian; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Neurology, 2020)
Background: Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods: Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as “appropriate”, “underdosed” and “overdosed” in conformity with the European Medicines Agency labelling. The effect of underdosing on the functional factor Xa plasma level on admission, the clinical stroke severity and the functional outcome after 3 months were investigated. Results: 254 patients with cerebral ischemia while on Factor Xa inhibitors were included. The dose regimen of the Factor Xa inhibitor was appropriate in 166 patients (65%), underdosed in 67 patients (26%) and overdosed in 21 patients (8%). Underdosing was associated with female sex, diabetes mellitus and higher CHA2DS2–Vasc scores. Underdosing independently predicted lower anti-Xa plasma levels on admission [median 69.4 ng/ml (IQR 0.0–121.6) vs. 129.2 ng/ml (65.5–207.2); p < 0.001], was associated with higher NIHSS scores on admission [median 5 (IQR 1–10) vs. 3 (1–7); p = 0.041] and worse functional outcome after 3 months (favorable outcome 26.9% vs. 46.9%; p = 0.025). Conclusion: One in three patients with ischemic stroke during treatment with oral Xa inhibitors used inappropriate dose regimens. Underdosing was associated with lower functional plasma levels, higher clinical stroke severity and worse functional outcome.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atrial fibrillation; Direct oral anticoagulants; Dose reduction; Plasma levels; Stroke

Leukoreduction system chambers are an efficient, valid, and economic source of functional monocyte-derived dendritic cells and lymphocytes - Pfeiffer, Isabell A.; Zinser, Elisabeth; Strasser, Erwin; Stein, Marcello F.; Dörrie, Jan; Schaft, Niels; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2013)
The demand for human monocyte-derived dendritic cells (moDCs), as well as for primary human B and T lymphocytes for immunological research purposes has been increased in recent years. Classically, these monocytes are isolated from blood, leukapheresis products or buffy coats of healthy donors by plastic adherence of peripheral blood mononuclear cells (PBMCs), followed by stimulation with granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-4, while lymphocytes are usually isolated from the non-adherent fraction (NAF) by magnetic cell sorting. However, donor-blood is a limited resource and not every blood bank offers leukapheresis products or buffy coats for laboratory use. Additionally, a leukapheresis is very expensive and also the generation/isolation of cells is time- and cost-intensive. To overcome some of these obstacles, we evaluated if low-cost leukoreduction system chambers (LRSCs), which arise after routine donor plateletpheresis procedures, and are usually discarded, would be an alternative and appropriate source of PBMCs to generate moDCs and to isolate lymphocytes. By analyzing the number and phenotype of immature and mature dendritic cells (DCs), as well as of B and T lymphocytes derived from LRSCs, we found all cells to be of high quantity and quality. Further investigations on DCs comprising transwell migration assays, allogeneic mixed lymphocyte reactions (MLR), cytokine secretion assays, and cytotoxic T cell induction assays revealed high migratory, as well as stimulatory capacity of these cells. In addition, DCs and T cells were efficiently electroporated with mRNA and showed characteristic cytokine production after co-culture, demonstrating LRSCs as an efficient, valid, and economic source for generation of moDCs and lymphocytes for research purposes. © 2013 Elsevier GmbH.
CRIS-Team Scopus Importer:2021-10-01
Keywords: B cell; Leukoreduction system chamber; Monocyte-derived dendritic cell; Peripheral blood mononuclear cell; T cell

MANAGEMENT OF INSUFFICIENT FUNCTIONAL ANTITHROMBOTIC ACTIVITY DURING TREATMENT WITH DIRECT ORAL ANTICOAGULANTS FOR STROKE PREVENTION - Macha, Kosmas; Stoll, Svenja; Siedler, Gabriela; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Minimal information for studies of extracellular vesicles 2018 (MISEV2018): a position statement of the International Society for Extracellular Vesicles and update of the MISEV2014 guidelines - Thery, Clotilde; Witwer, Kenneth W.; Aikawa, Elena; Jose Alcaraz, Maria; Anderson, Johnathon D.; Andriantsitohaina, Ramaroson; Antoniou, Anna; Arab, Tanina; Archer, Fabienne; Atkin-Smith, Georgia K.; Ayre, D. Craig; Bach, Jean-Marie; et al. (Journal of Extracellular Vesicles, 2018)
The last decade has seen a sharp increase in the number of scientific publications describing physiological and pathological functions of extracellular vesicles (EVs), a collective term covering various subtypes of cell-released, membranous structures, called exosomes, microvesicles, microparticles, ectosomes, oncosomes, apoptotic bodies, and many other names. However, specific issues arise when working with these entities, whose size and amount often make them difficult to obtain as relatively pure preparations, and to characterize properly. The International Society for Extracellular Vesicles (ISEV) proposed Minimal Information for Studies of Extracellular Vesicles ("MISEV") guidelines for the field in 2014. We now update these "MISEV2014" guidelines based on evolution of the collective knowledge in the last four years. An important point to consider is that ascribing a specific function to EVs in general, or to subtypes of EVs, requires reporting of specific information beyond mere description of function in a crude, potentially contaminated, and heterogeneous preparation. For example, claims that exosomes are endowed with exquisite and specific activities remain difficult to support experimentally, given our still limited knowledge of their specific molecular machineries of biogenesis and release, as compared with other biophysically similar EVs. The MISEV2018 guidelines include tables and outlines of suggested protocols and steps to follow to document specific EV-associated functional activities. Finally, a checklist is provided with summaries of key points.
EVALuna2:210608

Monitoring of direct oral anticoagulants plasma levels for secondary stroke prevention - Siedler, Gabriela; Macha, Kosmas; Stoll, Svenja; Plechschmidt, Johannes; Wang, Ruihao; Gerner, Stefan; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Thrombosis and Haemostasis, 2022)
Background: Patients with atrial fibrillation have a relevant risk for ischemic stroke despite the recommended use of direct oral anticoagulants (DOAC). The risk correlates with the functional DOAC plasma levels in clinical trials, but the value of their measurement in community use remains undetermined. Objectives: We aim to investigate the clinical implications and the prognostic value of DOAC plasma level measurement during steady state. Methods: In this observational clinical cohort study among patients with ischemic stroke and atrial fibrillation, 397 individuals on oral anticoagulants for secondary stroke prevention were included between 2016 and 2020. The functional DOAC plasma levels were measured during steady state. Early stroke recurrence within 3 months was recorded as the main outcome parameter. Results: Three hundred ninety-seven patients (201 female, mean age 78 [±9] years, median CHA2DS2VASc-Score 6 [interquartile range 5–7]) were included. Mean DOAC plasma trough level was 95.9 (±66.9) ng/ml. A high glomerular filtration rate (GFR) was an independent predictor of lower levels in a multivariate model (R coefficient: −0.174, P =.014). During follow-up, 10 patients (3%) suffered from early ischemic stroke recurrence despite the use of DOAC, while 10 clinically relevant bleeding complications occurred (3%). Ischemic stroke recurrence was associated with numerical lower plasma levels for patients on apixaban and dabigatran after propensity score matching. Conclusions: Monitoring of DOAC plasma levels could help to identify patients with increased risk for stroke recurrence and should be considered for certain subgroups, including patients with high GFR.
CRIS-Team Scopus Importer:2022-03-18
Keywords: atrial fibrillation; cardioembolic stroke; direct oral anticoagulants; ischemic stroke; secondary prevention

Multivariate Platelet Analysis Differentiates between Patients with Alzheimer's Disease and Healthy Controls at First Clinical Diagnosis - Wiest, Isabella; Wiemers, Tim; Kraus, Max-Joseph; Neeb, Heiko; Strasser, Erwin; Hausner, Lucrezia; Froelich, Lutz; Bugert, Peter (Journal of Alzheimer's Disease, 2019)
Background: Early diagnosis of Alzheimer's disease (AD) is challenging, and easily accessible biomarkers are an unmet need. Blood platelets frequently serve as peripheral model for studying AD pathogenesis and might represent a reasonable biomarker source. Objective: In the present study, we investigated the potential to differentiate AD patients from healthy controls (HC) based on blood count, platelet morphology, and function as well as molecular markers at the time of first clinical diagnosis. Methods: Blood samples from 40 AD patients and 29 age-matched HC were included for determination of 78 parameter by blood counting, platelet morphometry, aggregometry, flow cytometry (CD62P, CD63, activated fibrinogen receptor), protein quantification of nicotinic acetylcholine receptor α7 (nAChRα7) and caveolin-1 (CAV-1), and miRNA quantification (miR-26b, miR-199a, miR-335). Group comparison between patients and controls was performed in univariate and multivariate statistical analyses. Results: AD patients showed significantly lower aggregation response to ADP and arachidonic acid and significantly decreased CD62P and CD63 surface expression induced by ADP and U46619 compared to HC. Relative nAChRα7 and CAV-1 expression was significantly higher AD platelets than in HC. Multivariate analysis of 63 parameter revealed significant differences between AD patients and healthy controls. The best performing feature model revealed a sensitivity of 96.6%, a specificity of 80.0%, and a positive predictive value of 89.3%. No grouping could be achieved by using single parameter groups. Conclusion: Significant differences between platelet characteristics from AD patients and HC at the time of first clinical diagnosis were observed. The best performing parameter can be used as a blood-based biomarker for AD diagnosis in a multivariate model in addition to the standardized mental tests.
CRIS-Team Scopus Importer:2019-10-18
Keywords: Aggregometry; Alzheimer's disease; blood-based biomarker; platelet morphology

Nanoscale bioactive glass activates osteoclastic differentiation of RAW 264.7 cells - Detsch, Rainer; Rübner, Matthias; Strissel, Pamela; Mohn, Dirk; Strasser, Erwin; Stark, Wendelin J.; Strick, Reiner; Boccaccini, Aldo R. (Nanomedicine, 2016)
There is limited knowledge regarding differentiation of osteoclasts in the presence of nanoscale bioactive glass (nBG). This investigation examined increasing concentrations of 45S5 nBG and their influence on osteoclast differentiation.Different concentrations of 45S5 nBG were cultured up to 14 days with the murine RAW264.7 cell line and human primary monocytes cultured with M-CSF and RANKL.Culturing cells for 14 days with 500 ?g/ml nBG showed a viability of 100%; however DNA synthesis was reduced, supporting differentiation into osteoclast-like cells. Using RAW cells, activation of nine genes, including cell fusion genes, occurred in an nBG concentration dependent manner. Low concentrations of nBG increased expression of genes involved in commitment to cell fusion, whereas high concentrations increased gene expression supporting osteoclast-like differentiation.nBG enhances both RAW264.7 and human osteoclast differentiation. nBG controlled gene expression in a concentration dependent manner could reflect normal regulation during bone growth.
EVALuna2:15997

No Safety Concerns with cryopreserved Platelets Comment - Strasser, Erwin (Transfusionsmedizin, 2020)
CRIS-Team WoS Importer:2020-03-06

Recommendations for Therapeutic Apheresis by the Section "preparative and Therapeutic Hemapheresis" of the German Society for Transfusion Medicine and Immunohematology - Worel, Nina; Mansouri Taleghani, Behrouz; Strasser, Erwin (Transfusion Medicine and Hemotherapy, 2019)
The section "Preparative and Therapeutic Hemapheresis" of the German Society for Transfusion Medicine and Immunohematology (DGTI) has reviewed the actual literature and updated techniques and indications for evidence-based use of therapeutic apheresis in human disease. The recommendations are mostly in line with the "Guidelines on the Use of Therapeutic Apheresis in Clinical Practice" published by the Writing Committee of the American Society for Apheresis (ASFA) and have been conducted by experts from the DACH (Germany, Austria, Switzerland) region.
CRIS-Team Scopus Importer:2019-11-22

T-cell subsets in autologous and allogeneic peripheral blood stem cell concentrates - Strobel, Joachim; Möllmer, Ina; Zingsem, Jürgen; Hauck-Dlimi, Barbara; Eckstein, Reinhold; Strasser, Erwin (Vox Sanguinis, 2015)
Regulatory T cells (Tregs) and other T-cell subsets are of importance in the setting of autologous and allogeneic stem cell transplantations. We conducted a study to assess the content of peripheral blood stem cell concentrates and related apheresis parameters in the autologous and allogeneic setting.We characterized 53 donors, patients and peripheral blood stem cell concentrates (PBSC) regarding the content of CD45(+) cells, lymphocytes, CD3(+) cells, CD3(+) CD4(+) T cells, CD3(+) CD4(+) CD25(+) T cells, CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs and CD34(+) cells and calculated cell yields, recruitment factors and collection efficiency for all cell types. We compared allogeneic data with autologous data.Autologous PBSC show significantly lower concentrations of T-cell subsets compared to allogeneic PBSC (17,112/?l CD4(+), 14,858/?l CD4(+) CD25(+) and 1579/?l CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs in autologous compared to 65,539/?l CD4(+), 44,208(+) /?l CD4(+) CD25(+) and 5040/?l CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs in allogeneic PBSC, respectively), in contrast to CD34(+) concentrations (5342/?l CD34(+) in autologous compared to 2367/?l CD34(+) in allogeneic PBSC, respectively). Accordantly, all T-cell yields are lower in the autologous setting compared to allogeneic PBSC. However, recruitment factor and collection efficiency of all cell types are higher in autologous compared to allogeneic PBSC, but not all parameters differ significantly when groups are compared.T-cell subsets and especially Tregs are a substantial part of PBSC transplantation, as considerable recruitment during apheresis occurs. In large volume apheresis, the collection efficiency of Treg is comparable to that of CD34(+) cells, while recruitment factors are even higher.
EVALuna2:15982

Thrombin Generation in Fresh and Frozen-Thawed Platelet Poor Plasma - Is there a Difference? - Kausche, Lea Elisabeth; Adler, Werner; Zimmermann, Robert; Hackstein, Holger; Strasser, Erwin (Clinical Laboratory, 2020)
Background: Applicability of thrombin generation tests to clinical routine has been sought for many years. The aim of this study was to compare thrombin generation measured in fresh platelet poor plasma (f-PPP) and frozen-thawed platelet poor plasma (ft-PPP) to prove the consistency of results.
CRIS-Team WoS Importer:2020-07-17

Thrombocyte apheresis cassettes as a novel source of viable peripheral blood mononuclear cells - Cunningham, Sarah; Buchele, Vera; Brox, Regine; Strasser, Erwin; Hackstein, Holger (Transfusion, 2020)
BACKGROUND: Traditionally, white blood cells (WBCs) are collected from buffy coats or freshly drawn blood. However, the increasing demand for peripheral blood mononuclear cells (PBMCs) in the research phases of immunological therapy development makes it necessary to identify alternative sources of these cells. STUDY DESIGN AND METHODS: Leukapheresis products are cost intensive and not offered by all blood banks. Therefore, thrombocyte apheresis cassettes (TACs), plateletpheresis waste products, were investigated as a possible low-cost and easily accessible blood source for research laboratories. The recovery rate, phenotype, and functionality of WBC subsets from TAC are unknown and were investigated in comparison to frequently used blood resources via flow cytometry. RESULTS: On average, TACs provide 30.3 × 106/mL PBMCs, situating themselves between peripheral whole blood (WB; 5.35 × 106/mL) and leukoreduction system chamber (LRSC; 163.9 × 106/mL) yields. Frequencies of CD14, CD3, CD4, CD8, CD56, CD19, and CD11c positive cells in TACs correlate with normal proportions of WBC populations. Stimulation of TAC-derived PBMCs by lipopolysaccharide (LPS) and resiquimod (R848) showed no significant differences in expression levels of human leukocyte antigen (HLA)-DR, DQ, DP, and CD86 or cytokine secretion compared to other blood source derived PBMC. Following stimulation with LPS or R848, comparable levels of tumor necrosis factor-α, interleukin-10, and interleukin-1β could be measured between TAC, LRSC, and WB. Additionally, TAC-derived T cells retained their proliferation capability and were able to produce interferon-γ following T-cell receptor stimulation. CONCLUSION: TACs provide a cost-effective source of viable and functional human blood cells that can readily be used for clinical and laboratory investigations after plateletpheresis preparation.
CRIS-Team Scopus Importer:2020-03-27

Twelve-year survival and immune correlates in dendritic cell-vaccinated melanoma patients - Gross, Stefanie; Erdmann, Michael; Haendle, Ina; Voland, Steve; Berger, Thomas; Schultz, Erwin; Strasser, Erwin; Dankerl, Peter; Janka, Rolf Matthias; Schliep, Stefan; Heinzerling, Lucie; Sotlar, Karl; et al. (JCI Insight, 2017)
BACKGROUND: Reports on long-term (≥10 years) effects of cancer vaccines are missing. Therefore, in 2002, we initiated a phase I/II trial in cutaneous melanoma patients to further explore the immunogenicity of our DC vaccine and to establish its long-term toxicity and clinical benefit after a planned 10-year followup. METHODS: Monocyte-derived DCs matured by TNFα, IL-1β, IL-6, and PGE2 and then loaded with 4 HLA class I and 6 class II-restricted tumor peptides were injected intradermally in high doses over 2 years. We performed serial immunomonitoring in all 53 evaluable patients. RESULTS: Vaccine-specific immune responses including high-affinity, IFNγ-producing CD4+ and lytic polyfunctional CD8+ T cells were de novo induced or boosted in most patients. Exposure of mature DCs to trimeric soluble CD40 ligand, unexpectedly, did not further enhance such immune responses, while keyhole limpet hemocyanin (KLH) pulsing to provide unspecific CD4+ help promoted CD8+ T cell responses - notably, their longevity. An unexpected 19% of nonresectable metastatic melanoma patients are still alive after 11 years, a survival rate similar to that observed in ipilimumab-treated patients and achieved without any major (>grade 2) toxicity. Survival correlated significantly with the development of intense vaccine injection site reactions, and with blood eosinophilia after the first series of vaccinations, suggesting that prolonged survival was a consequence of DC vaccination. CONCLUSIONS: Long-term survival in advanced melanoma patients undergoing DC vaccination is similar to ipilimumab-treated patients and occurs upon induction of tumor-specific T cells, blood eosinophilia, and strong vaccine injection site reactions occurring after the initial vaccinations. TRIAL REGISTRATION: ClinicalTrials.gov NCT00053391. FUNDING: European Community, Sixth Framework Programme (Cancerimmunotherapy LSHC-CT-2006-518234; DC-THERA LSHB-CT-2004-512074), and German Research Foundation (CRC 643, C1, Z2).
EVALuna2:14632

Validation of a SARS-CoV-2 RNA RT-PCR assay for high-throughput testing in blood of COVID-19 convalescent plasma donors and patients - Strasser, Erwin; Steininger, Philipp; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger (Transfusion, 2020)
Background The frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia in blood donors is uncertain. Thus, assays for SARS-CoV-2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data.
CRIS-Team WoS Importer:2020-11-27

Vascular type Ehlers-Danlos syndrome is associated with platelet dysfunction and low vitamin D serum concentration - Busch, Albert; Hoffjan, Sabine; Bergmann, Frauke; Hartung, Birgit; Jung, Helena; Hanel, Daniela; Tzschach, Andeas; Kadar, Janos; Von Kodolitsch, Yskert; Germer, Christoph-Thomas; Trobisch, Heiner; Strasser, Erwin; et al. (Orphanet Journal of Rare Diseases, 2016)
BACKGROUND: The vascular type represents a very rare, yet the clinically most fatal entity of Ehlers-Danlos syndrome (EDS). Patients are often admitted due to arterial bleedings and the friable tissue and the altered coagulation contribute to the challenge in treatment strategies. Until now there is little information about clotting characteristics that might influence hemostasis decisively and eventually worsen emergency situations. RESULTS: 22 vascular type EDS patients were studied for hemoglobin, platelet volume and count, Quick and activated partial thromboplastin time, fibrinogen, factor XIII, von Willebrand disease, vitamin D and platelet aggregation by modern standard laboratory methods. Results show a high prevalence of over 50 % for platelet aggregation disorders in vascular type EDS patients, especially for collagen and epinephrine induced tests, whereas the plasmatic cascade did not show any alterations. Additionally, more than half of the tested subjects showed low vitamin D serum levels, which might additionally affect vascular wall integrity. CONCLUSION: The presented data underline the importance of detailed laboratory screening methods in vascular type EDS patients in order to allow for targeted application of platelet-interacting substances that might be of decisive benefit in the emergency setting.
EVALuna2:32779